Bullying Against Adolescents; An Anticipation Through Islamic Parenting Style In The Post Covid Era - Marlina, Yuli; Sulaeman, Maryam (International Journal of Research in Counseling and Education, 2024)
This study aims not only to reveal the phenomenon of bullying that occurs in educational community in the millennial era who are familiar with social media, but also to provide an  information on anticipating bullying for adolescents through Islamic parenting styles. The family as the first and foremost educator has played an important role in effort to minimize bullying among adolescents. It is necessary to apply the principles of Islamic education in the family. This study uses descriptive qualitative methods, which aims to make measurements and will help in seeing the fundamental relationship between empirical observations by seeking information about existing symptoms. The population in this study were all high public senior high school students and teachers  or the equivalent at Pare  in 2021. Non-random sampling approach with purposive sampling method is used based on a regional approach with the level/number of bullying that occurs in the area by determining special characteristics, It’s accordance with the research objectives and based on research problems. The survey found that most of the students are being victims, witnesses and perpetrators of bullying by peers. An anticipation of high bullying through Islamic style is expected to be able to prevent bullying on adolescents today.